2017
DOI: 10.1007/s00246-017-1605-x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in National Institutes of Health-Funded Congenital Heart Disease Research from 2005 to 2015

Abstract: In an era of ongoing need for research to enable evidence-based care for the expanding population with congenital heart disease (CHD), economic fluctuations have impacted research funding. We characterize trends in NIH-funded CHD research from 2005 to 2015. We searched the NIH RePORTER database from 2005 to 2015 using the terms “congenital heart” and “cardiac morphogenesis”. Projects were characterized by year, institute, mechanism, costs, type and topic, and funding trends were analyzed. From 2005 to 2015, NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Naturally, the use and study of analyzed drugs in this review demand accurate clinical trials. A trend analysis of NIH-funded clinical trials addressing CHD showed that nearly less than 0.45% of the studies were aimed at the pediatric population, compared with the remaining 99.95% of clinical trials for general cardiovascular disease [ 185 ]. In terms of the current challenges of clinical trials, we concur on maximizing the study of cohorts [ 186 ], increasing the sample size regardless of the management issues of younglings [ 170 ], and enrolling heterogeneous patients, thus avoiding any neglection of participants, e.g., trisomy-21 patients [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, the use and study of analyzed drugs in this review demand accurate clinical trials. A trend analysis of NIH-funded clinical trials addressing CHD showed that nearly less than 0.45% of the studies were aimed at the pediatric population, compared with the remaining 99.95% of clinical trials for general cardiovascular disease [ 185 ]. In terms of the current challenges of clinical trials, we concur on maximizing the study of cohorts [ 186 ], increasing the sample size regardless of the management issues of younglings [ 170 ], and enrolling heterogeneous patients, thus avoiding any neglection of participants, e.g., trisomy-21 patients [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, new drugs should be developed to target specific genomic characterizations and variations in the RAAS or adrenergic signaling pathways to better improve responses to treatment and eventually ventricular function and survival of patients with CHD [ 189 ]. Likewise, a personalized approach should be sought, from prenatal screening to planning during infancy and childhood, and an eventual transition to adulthood with a multidisciplinary combination of interventions, including surgical, pharmacological, and percutaneous options [ 190 ], consistent with the aim to boost the impact of investment on health-directed CHD research [ 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…The National Institutes of Health (NIH) has increasingly funded research projects for congenital heart disease (CHD) over the last decade. From 2005 to 2015, USD 991 million was awarded to 633 projects, mainly in basic or translational research focused on cardiac developmental biology [75]. In 2018, the Congenital Heart Futures Reauthorization Act was signed into law to enhance research and surveillance efforts at the Centers for Disease Control and Prevention and the NIH, specifically toward studying CHD across the lifespan [76].…”
Section: Reimbursement and Research Fundingmentioning
confidence: 99%
“…Remarkably, the National Institutes of Health (NIH) did not recognize CHDs as a funding category prior to 2016, making data on prior investments difficult to accurately quantify [ 21 ], but also further underscoring the lack of emphasis on this field. Since its inception, federal funding in CHDs has remained stagnant, with a nominal increase of less than 5% annually, whereas NIH investment in Alzheimer’s has increased an average of 27% each year over the same period [ 20 ].…”
Section: Funding Landscapementioning
confidence: 99%